2011
DOI: 10.1167/iovs.10-6356
|View full text |Cite
|
Sign up to set email alerts
|

Olfactomedin 2: Expression in the Eye and Interaction with Other Olfactomedin Domain–Containing Proteins

Abstract: Highly conserved OLFM2 protein may play an important role in the course of retinal and eye development. Severe mutations in one of the closely related olfactomedin domain-containing proteins (Olfm1-3) may block the secretion and probably the activity of all three family members, leading to more pronounced diseases of the retina than the knockout of individual genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…In these transgenic mice, EGFP expression in the developing and adult brain coincides with known sites of Olfm1 expression, as determined by in situ hybridization (4,24). Expression of Olfm1 reaches the maximum level between the late embryonic and the early postnatal stages, as judged by in situ hybridization and quantitative PCR (25). At the embryonic stage E13, EGFP expression was detected mainly in the neuronal tissues, with the highest levels of expression in the medulla oblongata, outer area of the midbrain, DRG, and spinal cord.…”
Section: Olfm1mentioning
confidence: 76%
“…In these transgenic mice, EGFP expression in the developing and adult brain coincides with known sites of Olfm1 expression, as determined by in situ hybridization (4,24). Expression of Olfm1 reaches the maximum level between the late embryonic and the early postnatal stages, as judged by in situ hybridization and quantitative PCR (25). At the embryonic stage E13, EGFP expression was detected mainly in the neuronal tissues, with the highest levels of expression in the medulla oblongata, outer area of the midbrain, DRG, and spinal cord.…”
Section: Olfm1mentioning
confidence: 76%
“…Olfm1 and Olfm2 are able to form heterodimers and available data suggest that they may perform similar functions (Sultana et al, 2011). Shotgun analysis of proteins constituting the AMPAR complexes demonstrated that Olfm1 and Olfm2 are the components of these complexes (Schwenk et al, 2012, Shanks et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…GAPDH was used for normalization. Primers for Q-PCR have been previously described (Sultana et al, 2011). Each sample was analyzed in triplicates.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations